Upaya Meningkatkan Kemampuan Motorik Halus Melalui Teknik Finger Painting Pada Anak Usia 4-5 Tahun DI PAUD Teratai I Desa Pinayungan Kecamatan Telukjambe Timur Karawang - Isna Siskawati; siti syarah (Sekolah Tinggi Agama Islam Publisistik Thawalib Jakarta, 2020)
This study aims to determine whether finger painting techniques can improve the fine motor skills of children aged 4-5 years in PAUD Teratai I Desa Pinayungan Kecamatan Telukjambe Timur Kabupaten Karawang. Fine motor skills are movements that only involve certain parts of the body and are performed by small muscles, such as the fingers and precise wrist movements. This research is a classroom action research, in which the researcher, Siti Syarah as a teacher in the classroom, applies a lesson in an effort to improve existing learning. The design of this study used the Kemmis and Mc. Taggart, held in the second semester of the 2019/2020 academic year, September-December 2019. The subjects of this study were 23 students aged 4-5 years. The object of research is fine motor skills. To obtain data, observation instruments were used using observation sheet guides, giving tests that referred to the process and student work results and documentation. Data analysis is descriptive, presented in the form of tables and graphs based on learning outcomes in each cycle by calculating the percentage using the formula P = f /n x 100%. The results showed that the fine motor skills of children from each cycle had increased, seen from the development of the BSB category where the pre-cycle conditions were 17%, then after learning through finger panting techniques increased 43% in cycle I and became 78% in cycle II. This increase has exceeded the minimum target with a percentage value of 75% of children's classical learning completeness.